Toward more sustainable tropical agriculture with cover crops: Soil microbiome responses to nitrogen management - Momesso, Letusa [UNESP]; Crusciol, Carlos A.C. [UNESP]; Bossolani, Joao W. [UNESP]; Moretti, Luiz G. [UNESP]; Leite, Marcio F.A.; Kowalchuk, George A.; Kuramae, Eiko E. (Elsevier, 2022)
Cover crops are a potential pathway for ecological cultivation in agricultural systems. In tropical no-till agricultural systems, the maintenance of residues on the soil surface and the addition of nitrogen (N) benefit the growth and grain yield of cash crops as well as the chemical and physical properties of the soil. However, the effects of these management practices on the soil microbiota are largely unknown. Here, we evaluated the effects of the timing of N application as a pulse disturbance and the growth of different cover crop species before maize in rotation on soil properties, maize productivity, and soil bacterial and fungal community diversity and composition. N fertilizer was applied either on live cover crops (palisade grass or ruzigrass), on cover crop straw just before maize seeding or in the maize V4 growth stage. Soils previously cultivated with palisade grass established similar microbial communities regardless of N application timing, with increases in total bacteria, total archaea, nutrients, and the C:N ratio. The soil microbial alpha diversity in treatments with palisade grass did not vary with N application timing, whereas the bacterial and fungal diversities in the treatments with ruzigrass decreased when N was applied to live ruzigrass or maize in the V4 growth stage. We conclude that palisade grass is a more suitable cover crop than ruzigrass, as palisade grass enhanced soil microbial diversity and maize productivity regardless of N application timing. Ruzigrass could be used as an alternative to palisade grass when N is applied during the straw phase. However, considering the entire agricultural system (soil–plant–microbe), ruzigrass is not as efficient as palisade grass in tropical no-till cover crop–maize rotation systems. Palisade grass is a suitable cover crop alternative for enhancing maize productivity, soil chemical properties and nutrient cycling, regardless of the timing of N application. Additionally, this study demonstrates that a holistic approach is valuable for evaluating soil diversity and crop productivity in agricultural systems.
Keywords: Agroecology; Bacteria; Crop rotation; Forage grasses; Fungi; no-till system; Soil biodiversity